Precariedade da vida nas experiências de aborto (I)legal após violência sexual - Fonseca, Tais Peres (2019)
According to the World Health Organization (WHO) sexual violence is a public health issue. In Brazil, besides a health issue, it is considered a crime foreseen by the Brazilian Penal Code since 1940. In cases where a pregnancy occurs, the applicant or practitioner who performs the abortion is not punished provided that the consent of the gestating person or his legal representative is given. According to the Information System of Notification of Disorders (SINAN), in 2017 there were 307,367 cases of domestic and / or sexual violence. And, according to the Brazilian Yearbook of Public Security (São Paulo, 2019), in 2018 there were 66,041 cases of sexual violence in Brazil. Given this context, this study aims to analyze the experiences engendered in the path of people who requested the legal termination of pregnancy in case of sexual violence hosted in the Program of Assistance to Victims of Sexual Violence - PAVIVIS in Vitória - ES. To this end, we initially conducted an Integrative Review of Brazilian scientific publications on legal termination of pregnancy after sexual violence between 2008 and 2018. Subsequently, a qualitative research was conducted through two narrative interviews with legal abortion claimants previously received and attended at PAVIVIS in Vitória - ES. For narrative analysis, the assumptions of Discourse Analysis were employed. As a result of the first stage of the research, a small number of publications related to the theme in Brazil were verified. Researchers feared criminalization and moral and religious precepts intervening in the practice of professionals and students when asked about legal abortion. Regarding those who requested legal abortion, according to the studies, there is shame, fear, disgust, guilt, impotence and anger in the face of the situation experienced. However, after the procedure, feelings of relief and satisfaction were found, without regrets. As for the second stage of the study, through narrative interviews it was possible to verify social, political and economic conditions as maximizing the precariousness of life. The reports show the need to lie, hide, justify or confess the violence experienced. Still, loneliness was observed during the journey as an experience related to the search for legal interruption of pregnancy. With this work, it is expected to broaden the discussion on the theme in different training and health care spaces